The impact of ownership structure on dividend policy of listed firms in Jordan - Hanady Bataineh (Cogent Business & Management, 2021)
This study investigates the impact of ownership structure on the dividend policy in Jordan. In particular, it aims to uncover the effects of family ownership, institutional ownership, foreign ownership, and state ownership on dividend decisions for a sample of 66 Jordanian industrial and service firms listed on the Amman Stock Exchange (ASE) for the period 2014-2017. Tobit Panel Regression is used to test the hypotheses of the study. The results show a significant positive association between institutional ownership and dividend yield, while foreign ownership is associated with a less likelihood of paying dividends. No evidence is found to support that family ownership and state ownership have an impact on dividend yield. Hence, the study provides a clear evidence that high institutional ownership as an external control mechanism increases the need to pay dividends. The results also indicate that Jordanian listed firms have highly concentrated ownership structures and are mainly dominated by families followed by financial institutions, then foreign investors while the state shows relatively lower ownership. The study recommends that investors should take into account ownership structure when making investment decisions to help them choose the best investment opportunities.
Keywords: 650; Dividends; Ownership; Tobit regression; Agency theory; Amman stock exchange